Effects of anxiety levels on learning performance and gaming performance in digital game‐based learning. (1st February 2018) - Yang, J. C.; Lin, M. Y. D.; Chen, S. Y.
Abstract: Anxiety plays an influential role in foreign language learning. However, a lack of attention was paid to examining the effects of anxiety levels on learning performance and gaming performance in digital game‐based learning. To this end, this study developed a game‐based English learning system and investigated how different levels of anxiety affected learners' learning performance and gaming performance. A quasi‐experiment was conducted in an elementary school. The results showed that high‐anxiety learners performed worse than low‐anxiety learners in speaking, word/sentence match, and overall learning performance. However, they performed similarly in listening performance. Moreover, the results showed that high‐ and low‐anxiety learners demonstrated a similar level of gaming performance. A subsequent analysis showed that significant correlations existed between learning performance and gaming performance for learners with high anxiety whereas such positive correlations were rarely found for learners with low anxiety, indicating that high‐anxiety learners' learning performance could be fostered by their gaming performance. The findings suggested that digital game‐based learning was particularly beneficial to high‐anxiety learners, whose gaming performance was a facilitative factor of their learning performance. Lay Description: What is currently known about the subject matter: Game‐based learning is useful to enhance student learning. What their paper adds: Game performance is associated with learning performance for learners. The implications of study findings for practitioners: Anxiety levels are essential human factors.